СИРОЖИДДИН САЙЙИД ИККИЛИК ШЕЪРЛАРИНИНГ ҒОЯВИЙ – ЭСТЕТИК МОҲИЯТИ - Дошанова, Г. (SCIENCE and SOCIETY, 2021)
Thes article analyzes examines the issues of dual poetic forms in the work of the modern poet Sirojiddin Sayyid. As well as the txspression of ideological and aesthetic essence in it. It also covers the poets individual style research and artistic skills.
Keywords: dual poetic forms; genre; artistic mastery; palindrome; metaphor; poetic style; didactic content